Beyond a Focus on Fuel Reduction in the WUI: The Need for Regional Wildfire Mitigation to Address Multiple Risks - Moritz, Max A.; Hazard, Rob; Johnston, Kelly; Mayes, Marc; Mowery, Molly; Oran, Katie; Parkinson, Anne-Marie; Schmidt, David A.; Wesolowski, Graham (Frontiers in Forests and Global Change, 2022)
There are thousands of communities and millions of homes in fire-prone wildland-urban interface (WUI) environments. Although future developments may be sited and designed to be more survivable and resistant to losses, an over-arching strategy is needed for those that are already at high risk. Traditionally, most plans for protecting WUI inhabitants focus on fuel reduction in strategic locations (e.g., defensible space around homes, fuel breaks around communities). While this approach can reduce fire hazard in specific locations and under certain weather conditions, there are a variety of vulnerabilities that are not directly addressed by fuel reduction. A more comprehensive approach is needed – one that facilitates climate change adaptation and future resilience – to mitigate multiple fire-related risks. A Regional Wildfire Mitigation Program (RWMP), expanding on traditional approaches to wildfire protection, is a key step in this direction. The goals of an RWMP include 1) retrofitting of the built environment (i.e., structural ignition vulnerabilities, water supply deficiencies, evacuation constraints); 2) buffering the landscape (i.e., a mosaic of less flammable land uses complementing traditional fuel breaks); and 3) training the community (i.e., education to become fire-adapted). We demonstrate here a consistent methodology for mapping hazards and vulnerabilities, assessing the risks of multiple negative impacts, prioritizing diverse mitigation activities, and implementing solutions that are effective and portable across many WUI environments.